Experimental investigation of crack initiation and propagation in high- and gigacycle fatigue in titanium alloys by study of morphology of fracture - M.V. Bannikov; O. B. Naimark; V.A. Oborin (Fracture and Structural Integrity)
Fatigue (high- and gigacycle) crack initiation and its propagation in titanium alloys with coarse and fine grain structure are studied by fractography analysis of fracture surface. Fractured specimens were analyzed by interferometer microscope and electronic microscope to improve methods of monitoring of damage accumulation during fatigue test and verify the models for fatigue crack kinetics. Fatigue strength was estimated for high cycle fatigue (HCF) regime using the Luong method [1] by “in-situ” infrared scanning of the sample surface for the step-wise loading history for different grain size metals. Fine grain alloys demonstrated higher fatigue resistance for both HCF and gigacycle fatigue regimes. Fracture surface analysis for cylindrical samples was carried out using optical and electronic microscopy method. High resolution profilometry (interferometerprofiler New View 5010) data of fracture surface roughness allowed us to estimate scale invariance (the Hurst exponent) and to establish the existence of two characteristic areas of damage localization (different values of the Hurst exponent). Area 1 with diameter ~300 ?m has the pronounced roughness and is associated with damage localization hotspot. Area 2 shows less amplitude roughness, occupies the rest fracture surface and considered as the trace of the fatigue crack path corresponding to the Paris kinetics.